How well is hypertension managed in the community? A population-based survey in a Brazilian city - Roberto X. Piccini; Cesar G. Victora
There is usually little information available on how well hypertensive individuals are managed at the community level. This survey measured the frequency of hypertension in a medium-sized Brazilian city by studying a cluster sample of 1657 adults aged 20-69 years. The 328 hypertensives (19.8%) answered a questionnaire on the knowledge and management of their condition. Two-thirds were aware of their status and more than half were on antihypertensive medication, but only one-third had their blood pressure under control. Physicians failed to advise a large proportion of their patients about the need to lose weight, take exercise, and quit smoking. Although laboratory tests were carried out in most patients, fundoscopy and chest X-rays were performed in fewer than 50%. Continued care by the same physician was the only factor significantly associated with compensated high blood pressure (relative risk for not having continued care = 1.35; 95% CI = 1.02-1.71). High levels of absenteeism, reduction of the work load, and early retirement were found among the individuals with high blood pressure.